Ultra-stable silica/exfoliated graphite encapsulated n-hexacosane phase change nanocomposite: A promising material for thermal energy storage applications. (1st July 2022) - Khanna, Sakshum; Paneliya, Sagar; Prajapati, Parth; Mukhopadhyay, Indrajit; Jouhara, Hussam
Abstract: In the current work, we demonstrate a simple, versatile, and scalable approach to synthesized silica encapsulated phase-change material (n-hexacosane) loaded between exfoliated-graphite nanosheets (ESPCM) by a chemical process (sol-gel and hydrothermal technique), exhibiting ultra-high thermal stability. The morphological, structural, and chemical properties of synthesized nanocomposite materials were investigated, and the results revealed that the PCM encapsulated within the silica shell was of diameters 120–220 nm and loaded in porous dendritic structures without any chemical reactions in phase change material. Further, the thermophysical properties such as latent heat, thermal conductivity, and stability of synthesized nanocomposites (ESPCM) were investigated by differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA). During melting and solidification cycles, a solid-liquid phase transition of ESPCM nanocomposite was observed at 57.9 °C and 48.1 °C with a latent heat of 126.7 J/g and 117.6 J/g respectively. The ESPCM composites exhibited high thermal conductivity (15.74 W/m K) and ultra-high stability against thermal degradation after 300 thermal cycles. Subsequently, COMSOL simulations were carried out to investigate the thermal performance (heat flow with respect to time) of ESPCM, where, on increasing the EG concentration in the nanocomposite, an enhanced heat flow process was observed. Highlights: -Ultra-stable PCM encapsulated silica in exfoliated graphite composite. -Insight towards the heat transfer process in ESPCM using COMSOL simulation. -ESPCM composite showed enhanced thermal conductivity around 15.47 W/m-K. -Exudation test of ESPCM confirms the ultra-stability of the composite. -Reduction in melting and solidification time of 40% and 36% as compared to PCM.